Gender diversity, governance and dividend policy in Brazil (REGE Revista de Gestão, 2020)
Purpose – Considering that the heterogeneity in the composition of deliberation and management bodies can promote a differentiated impact on earnings distribution policies of companies, the purpose of this paper is to examine the marginal influence of female participation on the board of directors and executive board regarding decisions associated with dividend policy in companies operating in Brazil. Design/methodology/approach – The sample is composed of non-financial companies listed on the B3 Stock Exchange between 2010 and 2015, which encompasses 261 companies (1,084 observations per year). The tests aim at explaining the probability of earnings distribution and the payout level of companies through variables that measure the female presence – considering that the explanatory economic attributes of decisions over dividends are kept under control. The econometric analysis was carried out through the descriptive analysis of the variables and LOGIT and TOBIT tests of inference estimated with fixed effects and meeting all econometric requirements. Findings – The proportion of women in both deliberative and executive bodies affects marginally the dividend policy of Brazilian companies. The female presence in management bodies contributes to a higher probability of earnings distribution and increase in the payout level; such tendency is moderated when women are in the board of directors; so, we do not reject the hypothesis of female influence on dividend policy decisions in Brazil. Originality/value – One can find such investigations in foreign environments, but such tests had not been accomplished in Brazil so far. We discuss, therefore, in an unprecedented way, the heterogeneity in deliberative (governance) and executive (management) bodies and its outcomes in strategic decisions made in Brazilian companies, focusing on the female insertion and on fundamental decisions that are related to the relationship among stakeholders, which is the dividend policy per se.